On the identity of Chamaepinnularia thermophila comb. nov. (Bacillariophyceae) from a Neotropical thermal spring - Wetzel, Carlos E.; Ector, Luc (Phytotaxa, 2016)
Navicula thermophila Manguin in Bourrelly & Manguin (1952: 60) was described from a hot saline spring in Guadeloupe (French Antilles). The species with diminutive proportions was described as follows: